Cosmic anger : Abdus Salam - the first Muslim Nobel scientist - Fraser, Gordon, 1943- (Oxford : Oxford University Press, 2008)
Abdus Salam was the first citizen of Pakistan to win a Nobel Prize, but he was branded as a heretic and excommunicated from his home country, where his achievements are often overlooked even besmirched. Instead, he acted out his dreams on a wider stage, as a citizen of the world.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Salam, Abdus, -- 1926-1996.; Physicists -- Pakistan -- Biography; Nobel Prize winners -- Pakistan -- Biography